Desain Sistem Kontrol Ruang Pertumbuhan Ulat Sutera untuk Meningkatkan Kualitas Produksi Sutera Alam - Lilik Sutiarso; Atris Suyantohadi; Hari Purwanto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2004)
The world demand of raw-silk provides a great opportunity to the development of raw-silk production in Yogyakarta. Recently, only 21% out of the overall world demand of raw-silk is fulfilled, whereas Indonesia contributes only 0.1% per year. The main problem is the lack of quality of raw-silk. The optimum growth of silkworm depends on micro environments, i. e. temperature, humidity, aeration, and light intensity. The research was aimed, to apply an automated -